Effectiveness of LinkedIn as a Personal Branding Platform in Increasing the Employment of Higher Education Graduates in Indonesia - Hidayah, Fathul; Putri, Aulia Melinda; Usman, Osly (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
In the digital era, job market competition is increasingly fierce, requiring university graduates to stand out. LinkedIn, as a professional networking platform, plays a strategic role in building personal branding to enhance graduate competitiveness and employment opportunities. This study analyzes the effectiveness of LinkedIn usage and the quality of professional content in improving graduate competitiveness and its impact on employment absorption. Using a quantitative approach, data were collected from 100 final year students and alumni through surveys and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that both LinkedIn usage and professional content quality significantly influence graduate competitiveness, which in turn positively affects employment absorption. Competitiveness also mediates the relationship between LinkedIn use and employment outcomes. This research contributes to digital career development literature and serves as a practical reference for graduates, institutions, and recruiters in leveraging LinkedIn for career advancement.